Pemanfaatan Mesin Power Thresher Untuk Peningkatan Produktivitas Pasca Panen Bagi Petani Di Desa Sempadian - Sundari, Ellys Mei; Jagat, Lang; Apriani, Winda (Sehati Abdimas, 2024)
Community Service (PKM) activities have been carried out with the aim of utilizing a power thresher machine that has been designed and made by the Sambas State Polytechnic PKM Team to be implemented by farmer groups in Sempadian Village, Tekarang District, Sambas Regency. The team implementing this activity is a group of lecturers with multi-disciplinary fields, namely Mechanical Engineering for machine manufacturing, Agricultural Machinery Engineering for engineering design and machine performance testing, and Multimedia Engineering for design drawings. Apart from that, this activity was also assisted by mechanical technicians and several active students who were directly involved in service activities both when making tools and applying them in the field. The target audience involved in this activity is the Kartini Women's Farming Group (KWT) in Sempadian Village. The KWT has 13 active farmers. The implementation of this activity uses the main method of community empowerment, in the form of direct practice methods in the field. Among them are the practice of using, caring for and maintaining machines, as well as the theory and practice of Occupational Safety and Health (K3). This activity is able to contribute knowledge and application of technology from the Sambas State Polytechnic, namely a power thresher as a form of technology adoption for the community and increasing public knowledge about post-harvest. The result of this activity is that farmers are able to apply the technology provided properly and correctly independently, namely in the form of operating machines, maintaining and repairing minor damage to rice threshing machines. The impact of this activity is to increase the effectiveness and efficiency of agriculture for the community so that it can improve the community's economy, especially farmer groups in Sempadian Village.